Politics and technology in the post-truth era - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973- (Emerald studies in politics and technology, 2019)
Advances in information and communication technology (ICT) have directly impacted the way in which politics operates today. Bringing together research on Europe, the US, South America, the Middle East, Asia and Africa, this book examines the relationship between ICT and politics in a global perspective.Technological innovations such as big data, data mining, sentiment analysis, cognitive computing, artificial intelligence, virtual reality, augmented reality, social media and blockchain technology are reshaping the way ICT intersects with politics and in this collection contributors examine these developments, demonstrating their impact on the political landscape. Chapters examine topics such as cyberwarfare and propaganda, post-Soviet space, Snowden, US national security, e-government, GDPR, democratization in Africa and internet freedom.Providing an overview of new research on the emerging relationship between the promise and potential inherent in ICT and its impact on politics, this edited collection will prove an invaluable text for students, researchers and practitioners working in the fields of Politics, International Relations and Computer Science.